Child Friendly Markets As A Means Of Public Learning Space For Children: Case Study at Kowen Market, Sidokarto, Godean, Sleman, DIY - Dien F Awaliyah; Dinik Fitri Rahajeng Pangestuti; Ihsan Pandu Tauladan; Anifa Nurhayati; Wahyu Lisma Siami (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
The child-friendly market is one of the programs that has begun to be developed in several markets in Indonesia. This program was designed to meet the needs of a safe, comfortable, and accessible environment for families, where children can play, learn, and interact with others while their caregivers carry out buying and selling activities. Child-friendly market is one of some agenda that support Sleman regency to withstand as a Child Friendly City and as a market that located in Sleman regency, Kowen market have the amenability to construct its environment as a child friendly market. Therefore, the aim of this study is to provide material for consideration for policy makers, in this case the management of Kalurahan Sidokarto in the discourse on establishing a child-friendly market at Pasar Kowen. This study is conducted with qualitative method that will be developed in an analytical descriptive manner. Researchers collected data through field research and literature research by applying a sociological approach to produce accurate data.